Globalisation and inequality: A dynamic general equilibrium model of unequal exchange - Roberto Veneziani; Naoki Yoshihara (University of Massachusetts, Department of Economics, 2016)
A dynamic general equilibrium model that generalises Roemer's [23] economy with a global capital market is analysed. An axiomatic analysis of the concept of unequal exchange (UE) between countries is developed at general dynamic equilibria. The class of UE definitions that satisfy three fundamental properties - including a correspondence between wealth, class and UE exploitation status - is completely characterised. It is shown that this class is nonempty and a definition of UE exploitation between countries is proposed, which is theoretically robust and firmly anchored to empirically observable data. The full class and UE exploitation structure of the international economy is derived in equilibrium.
Keywords: D63; F02; B51; 330; Exploitation; classes; unequal exchange; international economy; Marxismus; Soziale Schicht; Verteilungsgerechtigkeit; Internationale Wirtschaft